FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (Periode 2012-2014) - Septi Arianto, 12.05.52.0234; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the factors - factors that affect stock returns in manufacturing companies. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. The sampling technique is purposive sampling. Based on purposive sampling obtained a sample of 69 companies. Data analysis technique used is multiple linear regression analysis. The results of this study show that each variable has a different effect, namely EPS leave a positive and significant impact on stock returns, ROA positively influence and insignificant, while the DER, PBV, AG had a negative impact and no significant effect on stock returns. Keywords: Return On Assets (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS), Price to Book Value (PBV), Asset Growth (AG), and Stock Return